Grondslae van die reg op die reklamebeeld - Mostert, Frederick Willem (University of Johannesburg, 2015)
Keywords: Droit à l'image; Image rights; Publicidad; Publicitat; Publicité

Aanspreeklikheid van maatskappy-ouditeure teenoor derdes op grond van wanvoorstelling in die finansiële state - Pretorius, Joseph Thomas (University of Johannesburg, 2015)
Keywords: Auditing; Auditors; Commissaires aux comptes; Etat financier; Fausse déclaration; Financial statements; Liability (Law); Malpractice; Negligence; Responsabilité; South Africa

Die regsposisie van tydelike werknemers in diens van tydelike diensverskaffingsagentskappe - Botes, Anri (North-West University, 2013)
The use of temporary employment services as a means to achieve flexibility in die labour market led to various complications due to a lack of proper regulation. The atypical formation of the triangular employment relationship, limited rights and less favourable employment conditions of the temporary employees, multiple authority figures and their liabilities under various circumstances and the impact thereof on such employee’ collective bargaining rights caused legal uncertainty in the absence of sufficient legislation to govern it. Temporary employment agencies developed certain methods in order to evade the restrictive labour legislation and employer duties imposed on them, namely by making use of automatic termination clauses (resolutive conditions) and by categorising the temporary employee as an independent contractor. Last mentioned would effectively exclude the temporary employee from labour legislation and the protection it provides. In reaction to abovementioned problems, trade unions have been objecting to the use of temporary employment agencies and went as far as demanding the total ban thereof. This raised the question in the South African Government whether said agencies should indeed be banned. The other option is a less restrictive approach and entails the attempt to regulate these agencies by amending the current labour legislation in order to accommodate temporary employment services. In light of the fact that various proposals to amend the current South African labour legislation (especially with regard to temporary employment services) have been published in the Government Gazette, it can be deduced that the social partners ultimately chose to regulate temporary employment agencies rather than ban them altogether. From an early stage the International Labour Organisation (ILO) provided rules and regulations for the management of employment agencies in general by way of conventions and recommendations. In 1997, in order to give effect to the labour standards identified by it, the ILO brought the Private Employment Agencies Convention into existence. This document could be applied to all temporary employment agencies on an international level. This document provides for administrative regulations, the duties of the agency and the client as well as the rights of the temporary employees concerned. The ILO recommends that all of its member states incorporate the principles contained within this document in their own legislation. Temporary employment services are also used in other legal systems. For purposes of this study, the English law (United Kingdom (UK)) and the Namibian law will be scrutinised. Similar issues to those recognised in the South African law have been identified in these countries. However, each has approached said problems in different ways. The Namibian Government banned the conducting and provision of these services by way of legislation in 2007. The constitutionality of the ban has however been questioned by the Supreme Court of Namibia, after which it had been found to infringe upon the fundamental freedom to carry on any business, trade or occupation. The ban was struck down as unconstitutional. The Namibian Government has since promulgated new legislation in which it removed the ban and replaced it with numerous amendments providing for the regulation of temporary employment services. Since 1973 the UK has been promulgating various instruments for the thorough regulation of temporary employment agencies. These instruments provide for the management of temporary employment agencies and the rights of the employees involved. The relevant legislative instruments have been updated regularly with the purpose of ensuring that the needs of all the parties concerned are met. The UK, as a member state of the European Union (EU), (which has also been providing for the regulation of temporary employment services in various directives), promulgated legislation specifically with the aim to give effect to the principles in the mentioned directives. By way of doctrines and the creation of a third category ―worker‖ the UK has been attempting to prevent any loopholes in their legal system with regard to temporary employment services and the rights of the employees involved. The aim of this study is to investigate all the important complications experienced with temporary employment agencies in order to indicate the impact the atypical circumstances have on the rights of the temporary employees. The degree to which, if at all, the South African law complies with the preferred labour standards identified by the ILO will be pointed out. A comparative study will be conducted, first by ascertaining in detail how the comparable issues in the UK and Namibian law are dealt with, and second by identifying which aspects in these legal systems could be of value to the South African law. Finally the potential effectiveness of the proposed amendments to the South African labour legislation will be analysed, during which recommendations for the unresolved issues will be provided. The recommendations are mainly aimed at achieving sufficient rights and legal certainty for the temporary employees associated with temporary employment agencies.
Keywords: Arbeidsmakelaars; Atipiese diensverhoudinge; Buigsaamheid; Driehoekige diensverhouding; Flexibility; Independent contractor; Internasionale Arbeidsorganisasie; Job security; Onafhanklike kontrakteur; Temporary employees; Temporary employment agencies; Triangular employment relationship; Tydelike diensverskaffingsagentskappe; Tydelike werknemers; Ware werkgewer; Werksekuriteit

Die strafregtelike aanspreeklikheid van en straftoemeting aan regspersone - Du Toit, Pieter Gerhardus (North-West University, 2010)
Modern juristic persons often are powerful entities and they play an influential role in society. Their activities are often accompanied by serious transgressions that have a severely detrimental impact on human beings and their environment. The effective prosecution of juristic persons is therefore necessary. The juridical foundations of the liability of juristic persons are, however, one of the most controversial issues in criminal law theory. Individualistic theories postulate that juristic persons are merely collections of individuals. The conduct and fault of individuals constituting a juristic person must therefore form the basis of the criminal liability of the juristic person. In the United States, for instance, the foundation for the criminal liability of corporations on federal level is vicarious liability. Another individualistic model (mostly associated with English common law jurisdictions) is the so–called doctrine of identification. Only the conduct of individuals who are regarded as the 'directing minds' of the organisation may be attributed to the organisation. These approaches deny the complex structures and decision making processes that exist especially in big corporate entities. According to realistic theories juristic persons are entities which are not dependant on their composite members. Each juristic person has its own unique personality. The culture and ethos of a juristic person influence the conduct of individuals attached to it as well as the degree in which the juristic person abides by the law. The identity of a corporation can be established by investigating the internal structure thereof. The existence of monitoring mechanisms and educational programmes within the organization, as well as the degree to which the organisation condones or disapproves of unlawful conduct, are some of the factors which may be indicative of the corporate culture. This approach is a development of the late twentieth century and has recently been adopted in the legislation of some foreign legal systems, most notably Australia. Section 332(1) of the Criminal Procedure Act 51 of 1977 provides the basis for the criminal liability of juristic persons in South Africa. In essence the conduct and fault of functionaries (and sometimes even outsiders) are attributed to the juristic person. In terms of the provisions of the Criminal Procedure Act juristic persons may only be fined upon conviction. This approach reflects the individualistic view of corporate criminal liability. In this study recommendations are made for the purpose of improving the South African law in this regard so as to reflect a more realistic approach. The recommendations are based on an examination of realistic models proposed by legal and social theorists and legislation adopted by foreign countries which are based on these theories. It is also recommended that more sentencing options must be made available to bring about the restructuring of corporations which have committed crimes.
Keywords: Corporate culture; Corporate identity; Criminal liability; Doctrine of identification; Identifikasieleerstuk; Juristic persons; Korporatiewe identiteit; Korporatiewe kultuur; Middellike aanspreeklikheid; Organisasieteorie; Organisational theory; Regspersone; Sentencing; Strafregtelike aanspreeklikheid; Vicarious liability; Vonnisoplegging

Die ontwikkeling van die saaklike ooreenkoms by die oordrag van onroerende goed : 'n regshistoriese ondersoek - Schutte, Philippus Jacobus Wilhelmus (North-West University, 2007)
Keywords: Droit des biens; Propriété immobilière; Transfert